Implikasi perubahan kebijakan otonomi daerah terhadap beberapa aspek di sektor kehutanan: studi kasus di kabupaten Luwu utara, Sulawesi selatan - Ngakan, P.O.; Achmad, A.; Lahae, K.; Komarudin, Heru; Tako, A. (Center for International Forestry Research, 2007)
This report is based on a case study looking at the change in decentralization laws from the highly decentralized system under 22/1999 to a moderate system under 32/2004. It specifically analyses the implications of such change for local-level forest decision making processes related to forestry, spatial planning, shared revenues and village-level institutions in Luwu Utara district, South Sulawesi province. The research is a continuation of previous ACIAR/CIFOR collaborative research under the theme “Can Decentralization Work for Forests and the Poor?”. Results show that the revised law offers better mechanisms for coordination among government institutions, sharing governmental affairs and improving governance accountability. However, the delayed issuance of implementation regulation on division of authority has constrained local stakeholers to develop local policies. In the forestry sector, implementation of centrally as well locally designed programs is riddled with problems. There is still lack of coordination and a possibility for overlap of governmental duties between central, provincial and local forestry institutions e.g. implementation of national programme for forest and land rehabilitation, local and central government’s technical implementation units responsible for watershed management and forest area gazettment. Fragmentation of districts following decentralization has also changed Luwu Utara district and South Sulawesi province from rich-forest to poor forest local governments. Despite the substantial deficit in the forestry budget, indicated by low revenues and high expenditures, the local governments of Luwu Utara and South Sulawesi seem to commit to forest conservation. Village-level participation is accomodated through the central as well as local regulations on village autonomy. The effective implementation of village autonomy and regulations on natural resources, however, depends (and will depend) on the extent to which village institutions and local people’s capacity to take on the delegated duties and strengthen their institutions (through for example collective action). In addition, more importantly governments should not limit their role in issuing written rules, but extend to monitor the implementation and ensure that mechanisms for monitoring and sanctioning are in place. The report concludes that there has not been any significant impacts on local forestry sector following the change in decentralization laws; that division of authority for forest resources management remain unclear, and there is a tendency for overlap of duties. Despite some challenges, local governments have attempted to improve their accountability and transparency and there are potential synergy to foster intergovernmental relations through better coordination and capacity building.